Evaluation of marketing and commercial advertisements intended for the children public in the food practices of the brazilian population (Research, Society and Development, 2020)
Food marketing and advertising aimed at children influences the buying process of Brazilian families, persuading children with striking elements and being responsible for the increase in consumption of ultra-processed foods and the appearance of chronic non-communicable diseases (NCDs). Such action encourages consumption and induces families to associate foods with the image of well-being and happiness and consider them healthier than fresh foods. The present study aims to review the food labels of industrialized products aimed at children as regards the presence of abusive advertisements following the concept of abusive advertising in DRC No. 163/2014 of the National Council for the Rights of the Child and the Teenager (CONADA). The inclusion criteria were based on RDC No. 24/2010 and RDC No. 163/2014, being a qualitative research of the descriptive and exploratory type, with a theoretical approach and based on secondary data. Being identified the influence of advertisements in different aspects of infant feeding. Most of the articles (46.6%) were related to food advertisements broadcast on television. In all articles, the presence of abusive advertising was verified, and the persuasion strategies vary from the presence of children's characters to the use of colors more attractive to this audience. Such findings demonstrate the importance of regulating food marketing and advertising, with the participation of several sectors of society being important in the search for quality of life and health for children.